Development and materials characterization of hydrothermally grown niobium-doped BiVO4 for ciprofloxacin and methylene blue degradation - Kurnia, Nadiya Rifqah; Amanda, Tia; Nurfitria, Rima; Aflaha, Rizky; Widakdo, Januar; Rianjanu, Aditya (Greensusmater, 2025)
This study reports the synthesis and characterization of niobium-doped BiVO4 (NbX-BiVO4, X = 0, 2, 4, 6 mol%) photocatalysts via a hydrothermal method, aimed at enhancing the degradation of organic pollutants under UV irradiation. X-ray diffraction (XRD) analysis confirmed the preservation of the monoclinic BiVO4 structure in all samples, although minor secondary features were detected in doped compositions. Field emission scanning electron microscope (FESEM) imaging revealed progressively rougher, nanostructured surfaces with increasing Nb content, while UV-Vis and photoluminescence (PL) spectroscopy indicated modified band structures and reduced recombination rates. Photocatalytic performance was evaluated using ciprofloxacin (CIP) and methylene blue (MB) as model pollutants. For CIP, the highest activity was achieved by Nb6-BiVO4 (k value of 0.09 min‒1 g–1), attributable to enhanced charge separation and increased surface texture. In contrast, MB degradation favored the undoped BiVO4 (k value of 0.29 min‒1 g–1) due to stronger dye adsorption, despite the optical improvements in doped samples. The findings demonstrate that Nb doping improves BiVO4 photocatalytic activity through synergistic structural and electronic effects, with pollutant-specific responses highlighting the importance of matching catalyst design to target contaminant properties.